2020
DOI: 10.3389/fendo.2020.582870
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Diabetes and COVID-19: An Infectious Disease Spreading From the East Collides With the Consequences of an Unhealthy Western Lifestyle

Abstract: The pandemic of COVID-19, caused by the coronavirus, SARS-CoV-2, has had a global impact not seen for an infectious disease for over a century. This acute pandemic has spread from the East and has been overlaid onto a slow pandemic of metabolic diseases of obesity and diabetes consequent from the increasing adoption of a Western-lifestyle characterized by excess calorie consumption with limited physical activity. It has become clear that these conditions predispose individuals to a more severe COVID-19 with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 165 publications
(186 reference statements)
1
49
0
Order By: Relevance
“…The activation of the receptor for the advanced glycation end products (RAGE), which is also expressed in the lungs, produces a pro-inflammatory response via nuclear factor (NF)-κB, by increasing the NF-κBp65 expression and the degradation of IκB [ 73 ]. Accumulation of AGE could prime an exaggerated cytokine response to viral infection and ARDS [ 74 ]. It has also been suggested that SARS-CoV-2 could activate RAGE, a pattern recognition receptor that recognizes both pathogen-associated molecular patterns from microorganisms and danger-associated molecular patterns released by damaged cells [ 73 , 74 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of the receptor for the advanced glycation end products (RAGE), which is also expressed in the lungs, produces a pro-inflammatory response via nuclear factor (NF)-κB, by increasing the NF-κBp65 expression and the degradation of IκB [ 73 ]. Accumulation of AGE could prime an exaggerated cytokine response to viral infection and ARDS [ 74 ]. It has also been suggested that SARS-CoV-2 could activate RAGE, a pattern recognition receptor that recognizes both pathogen-associated molecular patterns from microorganisms and danger-associated molecular patterns released by damaged cells [ 73 , 74 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
“…Accumulation of AGE could prime an exaggerated cytokine response to viral infection and ARDS [ 74 ]. It has also been suggested that SARS-CoV-2 could activate RAGE, a pattern recognition receptor that recognizes both pathogen-associated molecular patterns from microorganisms and danger-associated molecular patterns released by damaged cells [ 73 , 74 ]. Infection with SARS-CoV-2 also perturbs the renin–angiotensin system, favoring angiotensin II receptor 1 activation and potentially transactivating RAGE [ 74 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded on the basis of experiments conducted more than a decade ago, in which knock-out of the ACE2 gene in mice resulted in a deficiency of pancreatic insulin secretion that was partially countered by increased glucose utilization in muscle. Furthermore, overexpression of ACE2 improved glycaemic control in a model of type 2 diabetes in mice [ 55 , 56 ]. It is also reported that insulin decreases the expression of ACE2 [ 57 ] and levels of ACE2 in urine and serum are increased in patients with diabetes and positively related to blood glucose and HbA1c levels [ 56 ].…”
Section: The Mechanisms Linking Diabetes and Covid-19mentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID19), a viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), recently emerged as a serious public health problem 1 2 . Currently, millions of people have been infected with SARS-CoV-2 worldwide.…”
Section: Introductionmentioning
confidence: 99%